Successful Removal of Giant Intrapericardial Paraganglioma via Posterolateral Thoracotomy - Yoko Yamamoto; Ken Kodama; Hiroyuki Yamato; Masashi Takeda (Case Reports in Surgery)
Intrapericardial paraganglioma remains a surgical challenge because of its hypervascular nature and firm adhesion to adjacent mediastinal structures. Here, we describe a 63-year-old female with a giant nonfunctioning intrapericardial paraganglioma tightly adhered to the left atrium. Marginal but complete resection of the tumor was achieved via right posterolateral thoracotomy. At the time of dissection between the tumor and the left atrial wall, we encountered massive hemorrhage leading to cardiac arrest. We were able to repair the wall laceration with minimal time under an optimal operative field, which avoids air embolism. She was discharged without complications and is currently in good health with no recurrence or metastasis for 15 months. Based on our experience, cardiopulmonary bypass should be considered, if surgeons are able to secure suitable sites for arterial and venous cannulations while right posterolateral thoracotomy is employed.